Syed Abul Hasan Ali Hasani an-Nadwi Tentang Keruntuhan Peradaban, Pandangan Hidup, dan Pendidikan Islam - Azhari Setiawan (University of Darussalam Gontor, Indonesia, 2017)
This article aims to explore Syed Hasan Ali Nadwi’s views on the decline of civilization and the notion of Islamic worldview. First, the author describes about Syed Hasan Ali Nadwi’s life in a short bio. Second, the author explores Syed Hasan Ali Nadwi’s views and thoughts about the essence beyond the civilizations, its glory and decadence. Then I will elaborate Syed Hasan Ali Nadwi’s point of view about the worldview of Islam, what are the substances of an Islamic worldview and how far the worldview could bring civilizations to certain glories and decadence. My point of view on this article is the stronger worldview that Muslims have, the stronger civilization Muslims could establish. It all depend on how Muslims face the crisis of knowledge and the loss of adab by the right ‘knowledge’, right ‘choice’, and right ‘action.’